Repurposing quinoline-based (metallo) drug leads for the treatment of Leishmania major-induced cutaneous leishmaniasis - Murwira, Takudzwa Emmanuel (Department of Molecular and Cell Biology, 2026)
Leishmaniasis is a vector-borne neglected tropical disease, of which cutaneous leishmaniasis is the most common form. There is a crucial need to develop new drugs for cutaneous leishmaniasis, as current drugs are sub-optimal due to parasite-specific drug resistance, drug-induced host toxicity and lengthy treatment. Repurposing existing drugs and/or compounds with established biological activity provides an attractive measure for antileishmanial drug development. For instance, N-heterocyclic molecules, such as quinolines and aminoquinolines, are commonly used as privileged scaffolds for developing antimalarial and anticancer drugs, which show enhanced activity when combined with metal complexes. This is exemplified by the iron-containing compound ferrocene, which has been shown to amplify the efficacy of several quinoline-based drug candidates. Accordingly, this study investigates the potential of repurposing ferrocenyl-quinoline compounds as potential drug candidates for the treatment of cutaneous leishmaniasis caused by Leishmania major LV39, focusing on in vitro antiparasitic activity and cytotoxicity, using murine and cell-based models of the disease. Four ferrocenyl-quinoline compounds consisting of the quinoline scaffold bonded to ferrocene via varying linkers (imino-alkyl, amino-alkyl, triazole amine and phenyl-alkene) were synthesised. The synthetic routes used to generate these compounds and their precursors consisted of nucleophilic aromatic substitution, Schiff base condensation, copper(I)-catalysed azide-alkyne cycloaddition and Mizoroki-Heck coupling. All the compounds were fully characterised using standard spectroscopic (1H,13C{1H} NMR and FT-IR spectroscopy) and analytical (mass spectrometry, melting point and elemental analysis) techniques. The four compounds and their precursors were assessed for their antileishmanial activity against the promastigote form of L. major LV39. The amino-alkyl and triazole amine-linked compounds were the most active (IC50 = 0.50 and 4.04 μg/ml, respectively), with the former being more active than the control drug amphotericin B (IC50 = 1.94 μg/ml). Generally, the four ferrocenyl-quinoline compounds had higher antileishmanial activity than their respective precursors. The cytotoxicity of the compounds was also assessed against the murine RAW 264.7 macrophage cell line, and all four compounds were observed to be more cytotoxic than amphotericin B (CC50 < 50 μg/ml). Although the amino-alkyl and triazole amine-linked compounds had the highest cytotoxicities (CC50 = 0.86 and 8.55 μg/ml, respectively), both compounds were more selective toward L. major promastigotes than their imino-alkyl and phenyl-amine counterparts (SI > 1), making them promising antileishmanial agents worthy of further investigation. This study not only delineates structure-based trends on antileishmanial activity but also demonstrates the significance of incorporating metals in drug design to enhance potency.